Nitrogen transformations and pools in N-saturated mountain spruce forest soils - Tahovská, Karolina (Jihočeská univerzita, 2012)
The size and the relative importance of the main soil N pools (microbial biomass N, NH4+, NO3-, DON) in N saturated mountain forest soils (The Bohemian Forest, Czech Republic) were assessed. Moreover, the influence of temperature on the net processes of microbial N transformation in soil (N mineralization, nitrification, N immobilization) was determined.
Nitrogen transformations and pools in N-saturated mountain spruce forest soils
Keywords: microbial N immobilization; net nitrification; net mineralization; ammonification; N pools; forest soil; N saturation; temperature